Islam dan Legitimasi Kekuasaan: Konstruksi Identitas Politik pada Kesultanan Awal Melayu : Penelitian - Choirun Niswah; Agustin, Amanda; Sari, Wulan; Ruki, Rahman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyse the role of Islam in legitimising political identity and kekuasaan in early Melayu kingdoms such as Samudera Pasai, Malaka, and Demak. This study employs a kualitatif methodology with pustaka research that is based on primary and secondary data related to Islamic politics and Melayu history. The study's findings indicate that Islam is more than just a religious system; it also provides political legitimacy that supports social, legal, and governmental structures in the Melayu world. Islam's legitimacy is based on three pillars: theological (Zillullah fil Ard), normative-hukum (syariat as the foundation of law), and sociocultural (asimilating Islamic law with local customs). The results of this study enhance understanding of Islamic politics in Nusantara and the warisan of the Melayu kesultanan in creating a religious-political alliance.